Development of Community Participation Model for Promoting Early Childhood Development in Children with Potential Developmental Delay: Ban Kluai Model, Sukhothai - Kittitongsophon, Wanrichada; Upavanich, Siriluk (Thai Journal of Nursing and Midwifery Practice, 2023)
This research and development aimed to develop and evaluate a community participation model to promote early childhood development in children with potential developmental delay in one subdistrict of Sukhothai Province. Sample groups were purposively selected: 60 caregivers of children with potential developmental delay and 9 stakeholders in the community. The research method comprised 5 steps, namely 1) Analysis of the situation in promoting early childhood development, 2) Design of the model of community participation to promote early childhood development in children with potential developmental delay, 3) Applying the tentative model to child caregivers and community, 4) Revising the community participation model for promotion of development in children with potential developmental delay by adding an educational method for elderly caregivers, and 5) Evaluation of the developed model. The instruments consisted of the community participation model for early childhood development in children with potential developmental delay and the Developmental Surveillance and Promotion Manual (DSPM). The data collection tools consisted of a focus group guideline and questionnaires on knowledge and behavior of the caregiver. Data were analyzed using descriptive statistics, content analysis, and paired t-test to compare the results before and after using the model. The results revealed that the community participation model consisted of several stakeholders such as child caregivers, teachers at the child development centre, responsible person at the local government organization, responsible person at the subdistrict health promoting hospital and public health volunteers. Six main activities were implemented, namely coordination, education, promotion of child development, monitoring and evaluation, consulting and spending quality time to promote child development. After implementing the model, it was found that caregivers had significantly increased knowledge and appropriate behavior (p< .05).